Tunneling High-Resolution Color Content through 4:2:0 HEVC and AVC Video Coding Systems - Wu, Yongjun; Kanumuri, Sandeep; Zhang, Yifu; Sadhwani, Shyam; Sullivan, Gary J.; Malvar, Rico (Data Compression Conference, 2013)
We present a method to convey high-resolution color (4:4:4) video content through a video coding system designed for chroma-subsampled (4:2:0) operation. The method operates by packing the samples of a 4:4:4 frame into two frames that are then encoded as if they were ordinary 4:2:0 content. After being received and decoded, the packing process is reversed to recover a 4:4:4 video frame. As 4:2:0 is the most widely supported digital color format, the described scheme provides an effective way of transporting 4:4:4 content through existing mass-market encoders and decoders, for applications such as coding of screen content. The described packing arrangement is designed such that the spatial correspondence and motion vector displacement relationships between the nominally-luma and nominally-chroma components are preserved. The use of this scheme can be indicated by a metadata tag such as the frame packing arrangement supplemental enhancement information (SEI) message defined in the HEVC (Rec. ITU-T H.265 | ISO/IEC 23008-2) and AVC (Rec. ITU-T H.264 | ISO/IEC 14496-10) video coding standards. In this context the scheme would operate in a similar manner as is commonly used for packing the two views of stereoscopic 3D video for compatible encoding. The technique can also be extended to transport 4:2:2 video through 4:2:0 systems or 4:4:4 video through 4:2:2 systems.